Pengaruh Penerapan Green Accounting dan Perputaran Total Aset Terhadap Profitabilitas - Utami, Retno Dwi; Nuraini, Airin (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The purpose of this research is to find out the influence of Green Accounting implementation and total asset turnover to profitability applied by foreign mining companies in Indonesia. While these companies play an important role in industry, they exploit natural resources and environment to raise their standards and earn maximum profits without concerning the surrounding conditions. The companies’ activities that cause negative impacts on society can reduce the investors’ trust and will eventually destroy their own image. Mining companies apply the Green Accounting concept in order to overcome the risks of natural disasters caused by their activities. The samples of this study include 5 foreign mining companies that have been operating in Indonesia for 6 years. Sample collection uses Non-probability sampling method and purposive sampling technique. Various methods of data analysis are performed to process the collected data to prove the effects of the two independent variables on the dependent variable. The results of this study show that the application of Green Accounting partially has no effect on profitability of the mining companies because social and environment costs are not transparent in their financial statements. However, Total Asset Turnover partially affects the profitability of the companies and tends to increase every year. The application of Green Accounting and Total Asset Turnover simultaneously affect the profitability of the mining companies as the environmental condition needs to be considered in carrying out their operations. As a result, environmental performance has a significant influence on the companies’ finance. Keywords: Green Accounting, Total Asset Turnover, and Profitability